IFLA's First Fifty Years : Achievement and Challenge in International Librarianship. - Koops, Willem Roelf Henderikus. (IFLA Publications, 1977)
The International Federation of Library Associations and Institutions (IFLA) is the leading international body representing the interests of library and information services and their users. It is the global voice of the information profession. The series IFLA Publications deals with many of the means through which libraries, information centres, and information professionals worldwide can formulate their goals, exert their influence as a group, protect their interests, and find solutions to global problems.